Rick Steves' European Christmas [videorecording (DVD)] - Steves, Rick, 1955- (Back Door Productions, 2005)
Join Rick Steves as he celebrates European Christmas traditions and music in England, Norway, France, Germany, Italy, and the Swiss Alps.